LncRNA CHRF: molecular mechanisms and therapeutic potentials in cardiovascular diseases, cancers and fibrosis - Mou, Jie; Luo, Chuntao; Zhang, Wen; Shao, Yin; Pei, Juan; Chen, Yaqin; Guo, Xin; Fan, Yonghong; Sun, Hongyu (Frontiers in Cell and Developmental Biology, 2025)
Long non-coding RNAs (LncRNA), exceeding 200 nucleotides in size, have emerged as important regulators of genes involved in multiple biological functions including cell growth, migration, invasion, drug resistance and apoptosis. They are increasingly being explored in human diseases. Notably, the recently identified LncRNA Cardiac hypertrophy-related factor (CHRF) has gained attention for its involvement in the molecular mechanisms of various diseases. CHRF was originally identified as a contributive LncRNA in cardiovascular diseases. Subsequent studies also revealed that it exerts an important role in promoting fibrosis and drug resistance. However, CHRF exhibits oncogenic functions in numerous cancers, including Non-small cell lung cancer (NSCLC), Colorectal cancer (CRC), Ovarian cancer (OC), Gastric cancer (GC), indicating its crucial roles in cancer progression. CHRF exhibits tremendous potential as both therapeutic target and diagnostic biomarker, particularly in cardiomyopathy, fibrosis, and cancer. To enhance our comprehensive understanding, this review synthesizes the pathophysiological mechanisms associated with CHRF and discusses its biological significance and clinical implication. Additionally, This review provides a comprehensive discussion on therapeutic strategies based on Non-coding RNA targets and discuss the potential of targeting CHRF, which is expected to offer readers a research approach for identifying the correct target strategies.